Characterizing Reflective Diary Writing as an Argumentative Activity Type - Svačinová, Iva (Informal Logic)

(untitled) (Informal Logic, 2022)
This paper is focused on the practice of unsolicited, reflective diary writing as an act of externalizing internal dialogue. I suggest that it should be analyzed as an argumentative practice from the point of view of pragma-dialectics. In the first part of the paper, I demonstrate that internal communication can be examined from the perspective of pragma-dialectics because it is in line with its meta-theoretical principles (especially socialization and externalization). In the second part, I suggest that reflective diary writing should be conceived of as an argumentative activity type. I show that this practice is a conventionalized activity type that is preconditioned by implicit norms governing the conduct of argumentation.